L’incidence de l’anémie chez les gestantes en pré-opératoire au niveau de l’établissement hospitalier spécialisé mère et enfant de Laghouat - HAMAIDI Hayat; ZAITRI Aicha (Université Amar Télidji Laghouat, 2022)
Introduction: Anemia is a subsequent health problem, which affects in particular newborn babies and pregnant women alike. To better investigate the issue and its side effects that might have on such study population, we have carried out a multiple study case in our research to primarily determine the incidence of anemia and pre-diagnose materno-fetal prognosis for efficient antenatal care Methods: On this part of the current study, an explanation of systematic methods and appropriate devices is provided in order to validate and prove our data in a proper way. In this regard, for the sake of accomplishing the desired objectives, a perspective, descriptive , and transversal case study is adopted all along our reasearch, as scheduled by Lagouat Maternity Hospital ,in short-term programme over two months between June ,21 and September, 20 ,2021 ,Out of 550 pregnant women with pernicious anemia , we registered over the study period , 310anemicpregnancy cases who underwent caesarian operation or hysterectomy or uterus removal , that is to say an incidence 56,4% The average age of pregnant women is 31.5 years with extremes between the ages of 18 and 49 years , at Prenatal clinical supervision was almost not ordered on time ,in the sense that 76% of mothers received irregular medical examinations within the period of pregnancy where as 08% received no prenatal check-up at all , nor did they have clinical therapy at hostiptalising services . Malnutrition(80.6%) , food shortage and lack of nutritious ferro-folic supplement in mother’s daily diets(68.4%) , in addition to socio-economic factors and weak purchase power(60%), are regarded the major causes of anemic aspects in pregnant ladies we dealt with at Healthcare Centre across the municipality of Lagouat. A great importance was given in our study to nulliparous and paucigestes ,at 69% and 38.7 % respectively as the most reliable variables in sample group of the study case .Anemia must have been associated to the interval birth-period between the current and previouspregnancies 107 , apparently estimated by less than two years in about 57,5 %pregnant mothers , 30% were primigestes. Asthenia and mucocutaneous pallor seem to be the apparent clinical symptoms amongst the pregnant women ,but in varied proportions, and at 30% ,and 42.2 % respectively. Hymogram is a biological test that is assigned to diagnose and permanently check any expected types of anemia .Decrease in HB proportion may help jeopardise the patients with anemic symptoms and expose to fatal death tolls . Anemia tensity varied from one group to another 62.2% of the study population developed low antenatal anemic disorders , whereas 4.2% had a very tense or fatal anemia .The type of hypochromic and microcytic anemia is the most common one and proved efficiently about 59% of the cases we conducted in the Maternity Centre , where deficiency in ferro-folic supplement appeared to be the leading cause of pregnant women's anemia. To lessen anemic symptoms, blood transfusion was afforded for a good number of patients estimated at 21.3%; ferro-folic drugs and supplements were prescribed too. The main fetal implications were PPH (1.3%), PP (1.3%), and while fetal mortality was by 01% of the study cases, prematurity implications go beyond 1.5%; IUGR cases jumped by 0.3, and IUDF implications rose by 1.5 %. Conclusion A regular and quality prenatal supervision must be undertaken for all pregnant women to lessen the occurring risks and detect anemic signs or symptoms for an adequate management and hence better materno-fetal prognosis. Keywords: Pregnancy, pregnant women,incidence, ferro-folic supplemdents , Lagouat
CD-ROM